Comprehensive assessment of host responses to ionizing radiation by nuclear factor-κB bioluminescence imaging-guided transcriptomic analysis. - Chung-Ta Chang (Public Library of Science (PLoS), 2011)
The aim of this study was to analyze the host responses to ionizing radiation by nuclear factor-κB (NF-κB) bioluminescence imaging-guided transcriptomic tool. Transgenic mice carrying the NF-κB-driven luciferase gene were exposed to a single dose of 8.5 Gy total-body irradiation. In vivo imaging showed that a maximal NF-κB-dependent bioluminescent intensity was observed at 3 h after irradiation and ex vivo imaging showed that liver, intestine, and brain displayed strong NF-κB activations. Microarray analysis of these organs showed that irradiation altered gene expression signatures in an organ-specific manner and several pathways associated with metabolism and immune system were significantly altered. Additionally, the upregulation of fatty acid binding protein 4, serum amyloid A2, and serum amyloid A3 genes, which participate in both inflammation and lipid metabolism, suggested that irradiation might affect the cross pathways of metabolism and inflammation. Moreover, the alteration of chemokine (CC-motif) ligand 5, chemokine (CC-motif) ligand 20, and Jagged 1 genes, which are involved in the inflammation and enterocyte proliferation, suggested that these genes might be involved in the radiation enteropathy. In conclusion, this report describes the comprehensive evaluation of host responses to ionizing radiation. Our findings provide the fundamental information about the in vivo NF-κB activity and transcriptomic pattern after irradiation. Moreover, novel targets involved in radiation injury are also suggested.